ANALISIS MUTU FISIK DAN SENSORI PREMIX KERNEL SEBAGAI FORTIFIKAN BERAS FORTIFIKASI - Feri Kusnandar; Masita Ardi Kumalasari; Antin Suswantinah; Safrida Safrida; Slamet Budijanto (AGROINTEK, 2021)
Premix kernel as fortificant on the rice fortification has a very important role for the success of the fortification program. The important aspect of premix kernel besides the uniformity of micronutrient content is also mostly determined by its physical and sensory properties. The aims of this study were to determine the effect of process temperature and water addition to the physical and sensory properties of the premix kernel produced. The experiment used a factorial completely randomized design with factor (1) extruder temperature (90, 95, and 100oC) and factor (2) water addition (35, 40, and 45%). Premix kernel (1 kg) was made from rice flour (800 g), sago starch (200 g), glycerol monostearate (20 g), and iron (7000 mg) using hot extrusion technology. The results showed that the process temperature had a significant effect on the parameter of brightness, hue, length, width, and thickness of the premix kernel, while the addition of water had significant influence on all aspects of the tested parameters including brightness, hue, 1000-grain weight, length, width, and thickness of the premix kernel. Interaction of process temperature and addition of water also have a significant effect on hue parameters, 1000-grain weight, length, width, and thickness of the premix kernel. The interaction of process temperature and addition of water also significantly influenced the hue parameter, 1000-grain weight, length, width, and thickness of the premix kernel. The combination of 90°C process temperature treatment and 40% water addition produced the highest frequency for all test parameters. The triangle test showed that panelists could not distinguish the fortified rice with commercial rice in the form of both cook and uncooked rice.